ANALISIS KETERAMPILAN PROSES SAINS MAHASISWA PADA MATA KULIAH BIOLOGI LINGKUNGAN PRODI BIOLOGI FAKULTAS SAINS DAN TEKNOLOGI - Adriadi, Ade; Ihsan, Mahya; Wulandari, Tia; Suprayogi, Dawam; Rayani, Nanda (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This study aims to analyse the Scientific Process Skills of students of FST UNJA’s Biology Programme in Environmental Biology when working on an eco-enzyme production project. This study, carried out in the FST UNJA Biology Programme. The research subjects are students from the FST UNJA Biology Programme who have taken Environmental Biology. Data in terms of students’ basic science process skills were obtained from the performance assessment of the eco-enzyme production project. The implementation of this research uses a Project Based Learning (PjBL) model. The results showed that students’ scientific process skills were generally in the very good and good categories, 54.7% and 41.02% respencipectively, while the remaining 2.3% of students had poor scientific process skills and 1.5% had no scientific process skills.